2018
DOI: 10.4066/biomedicalresearch.29-18-887
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular endothelial growth factor and mesenchymal stem cells during angiogenesis

Abstract: Objective: Angiogenesis is essential for bone remodeling and regeneration. We previously showed that 3 months after transplantation of mesenchymal stem cells (MSCs) into a bone defect area, significantly more regenerated bone was present on the MSC side than on the control side. On the side transplanted with MSCs, the number of blood vessels was significantly higher. Therefore, during the remodeling process, MSCs, which are necessary for regenerating bone, were involved in bone regeneration through angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…As the immobilized VEGF content increases, the number and length of the lumen-like structures raises as well. However, one previous study conducted by Oki et al [49] investigated the effect of soluble VEGF on the formation of HUVEC tubular structures and showed that lumens were not formed in systems subjected to soluble VEGF 50 ng ml −1 . However, in our study by immobilizing VEGF on the sheets, we observed the lumen-like structures of HUVECs.…”
Section: Formation Of Lumen-like Structuresmentioning
confidence: 97%
“…As the immobilized VEGF content increases, the number and length of the lumen-like structures raises as well. However, one previous study conducted by Oki et al [49] investigated the effect of soluble VEGF on the formation of HUVEC tubular structures and showed that lumens were not formed in systems subjected to soluble VEGF 50 ng ml −1 . However, in our study by immobilizing VEGF on the sheets, we observed the lumen-like structures of HUVECs.…”
Section: Formation Of Lumen-like Structuresmentioning
confidence: 97%
“…MSCs have been used in many studies due to their abilities to promote vessel formation and maturation by different mechanisms ( Navone et al, 2014 ; Oki et al, 2018 ). The MSCs produce pro-angiogenic cytokines such as hypoxia-inducible factor 1α (HIF-1α), angiogenin, angiopoietin I, angiopoietin II, angiopoietin IV, interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), insulin-like growth factor 1 (IGF-1), VEGF, bFGF, PDGF, transforming growth factor-β (TGF-β), monocyte chemoattractant protein-1 (MCP-1), and as well as by triggering the VEGF-A signaling cascade.…”
Section: Supporting Cellsmentioning
confidence: 99%
“…Transplanted MSCs can contribute to bone regeneration through angiogenesis stimulation [ 242 ]. hMSCs reside in hypoxic perivascular niches [ 243 ], express HIF-1α in response to hypoxic condition in defect site [ 244 247 ], and induce the expression of angiogenic factors such as VEGF, TGF-β, SDF-1, and stem cell factor (SCF) [ 248 ]. The studies showed that VEGF plays an important role in neovascularization and angiogenesis during the development of most tissues including bone [ 249 , 250 ].…”
Section: Introductionmentioning
confidence: 99%